Can green finance and environmental regulations promote carbon emission reduction? Evidence from China - Yin, Jin; Ibrahim, Saifuzzaman; Mohd, Naseem Niaz Ahmad; Zhong, Cheng; Mao, Xiaoming (Springer Science and Business Media, 2024)
Carbon reduction has become a major challenge for China's economy in its transition toward sustainability. The government has been monitoring the behavior of enterprises through regulations to protect the environment, while green finance has rapidly developed in recent years as a new tool to reduce carbon emissions. Despite these measures, few studies have explored the interaction between these two drivers of carbon reduction. Therefore, this study aimed to examine the impact of green finance and environmental regulations on carbon emissions. To determine whether their coordination can lead to greater carbon reduction, the spatial spillover effect of this impact was also investigated. The results show that green finance can reduce carbon emissions and that the interaction of green finance with environmental regulations plays a significant positive role in reducing carbon emissions. Finally, this study concludes that the carbon reduction effects of green finance and environmental regulations have positive spillover effects on adjacent areas. © 2023. The Author(s), under exclusive licence to Springer-Verlag GmbH Germany, part of Springer Nature.